Offshoring to Tax Heavens before and in the Time of Crisis: Role of Asian vs. European and American Tax Heavens - Folfas, Paweł (Przenoszenie działalności korporacji transnarodowych do rajów podatkowych: porównanie roli azjatyckich rajów podatkowych z europejskimi i amerykańskimi przed obecnym kryzysem i w czasie jego trwania, 2010)
Tax heavens play significant role in the expansion of transnational corporations (TNCs). Due to foreign direct investments in tax heavens and establishing in them foreign subsidiaries or even parent companies by TNCs, tax heavens have become flourishing offshore financial centres important for the world economy. Establishing related parties in the offshore financial centres brings TNCs handsome benefits such as: reducing tax burdens, enhancing cash flows and relative high efficiency of risk management. Particularly, the role of / Asian tax heavens is scrutinized. Hong Kong and Singapore have appeared for many years as TNCs' favourite locations. Current economic crisis has become a challenge also for tax heavens, while offshore financial centres are especially exposed to financial turbulences.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 412-424
Keywords: foreign direct investments (FDI); offshoring; tax heavens; Asian offshore financial centres